Development of an Electrochemical Oxygen Sensor for Liquid Sodium Using a Yttria Stabilized Zirconia Electrolyte. Issue 2 (6th December 2016) - Nollet, B. K.; Hvasta, M. G.; Anderson, M. H.; Morgan, D.; Schneider, J. A.
Abstract : An accurate means of measuring oxygen concentration in sodium is crucial to characterizing the corrosion of sodium-cooled fast reactor (SFR) materials. Significant improvements with regards to lifetime/sensitivity/temperature threshold/etc. can be made to current Galvanic-cell oxygen sensing technology, so extensive research has been conducted at the University of Wisconsin-Madison to address these issues. Electrochemical oxygen sensors using yttria-stabilized zirconia (YSZ) electrolytes were designed and tested in liquid sodium up to 400[°C]. These sensors produced an oxygen-dependent signal, and this signal followed the expected functional form, but the lifetime and reproducibility of the sensors were inadequate for commercial use. Sensor performance was analyzed and temperature effects on ionic conductivity, non-bulk thermodynamics, and YSZ-based issues were quantified to study deviations from theory in both slope and signal offset.